ANALISIS DAYA SAING KOMODITAS UNGGULAN TANAMAN PANGAN DI PROPINSI SUMATERA BARAT - Ilham Martadona; Khori Suci Maifianti (Universitas Teuku Umar, 2019)
The agricultural sector is one of the largest sectors in the formation of Sumatra Province GRDP West. The agricultural sector is dominated by the food subsector after the plantation subsector. Productivity of food crops tends to increase every year. The purpose of the study 1) to analyze the superior commodities of food crops in West Sumatra Province, 2) to analyze the trends in the harvested area of food crops of the West Sumatra Province. The LQ analysis is used to calculate the main commodities of food crops, while the analysis is trend to measure the development of the wide range of crop commodities. The results of the study indicate that the commodity of rice and sweet potato is a superior commodity in West Sumatra Province. Main commodities of paddy and sweet potato have increased annual harvest area of 11,844.50 ha and 258 ha.